This Is My Baby Interview: An Adaptation to the Spanish Language and Culture - Elena Pinero-Pinto; María-Luisa Benítez-Lugo; Raquel Chillón-Martínez; Isabel Escobio-Prieto; Gema Chamorro-Moriana; José-Jesús Jiménez-Rejano (Children, 2022)
Evaluating the emotional state of parents is important for determining the intervention in the context of a family with a baby with Down syndrome. “This is my baby” is an interview that measures the acceptance, commitment and awareness of influence of parents towards their baby. The Spanish adaptation of this instrument helps to better understand the emotional state of parents of children with developmental disorders. A cross-cultural adaptation and reliability analysis was carried out. The results suggest that the Spanish version of the This Is My Baby interview is a reliable instrument to measure the levels of acceptance, commitment and awareness of influence of parents of an infant with Down syndrome.